2014
DOI: 10.1002/pmic.201300558
|View full text |Cite
|
Sign up to set email alerts
|

MALDI imaging mass spectrometry to investigate endogenous peptides in an animal model of Usher's disease

Abstract: Imaging MS (MSI) has emerged as a valuable tool to study the spatial distribution of biomolecules in the brain. Herein, MALDI-MSI was used to determine the distribution of endogenous peptides in a rat model of Usher's disease. This rare disease is considered as a leading cause of deaf-blindness in humans worldwide. Cryosections of brain tissue were analyzed by MALDI-MSI to differentiate between healthy and diseased rats. MSI results were highly reproducible. Tissue-specific peptides were identified by MS/MS us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…MSI also showed a significant increase of endogenous peptides in rats models for Usher's disease, a rare cause of deaf‐blindness. These biomarker candidates were particularly present in the upper colliculi and in the substantia nigra of sick rats . MSI analyses of lenses revealed an increase in sphingomyelin levels, which may have an impact on development of age‐related nuclear cataract .…”
Section: Applications Of Msi In the Understanding Of Pathogenesismentioning
confidence: 99%
“…MSI also showed a significant increase of endogenous peptides in rats models for Usher's disease, a rare cause of deaf‐blindness. These biomarker candidates were particularly present in the upper colliculi and in the substantia nigra of sick rats . MSI analyses of lenses revealed an increase in sphingomyelin levels, which may have an impact on development of age‐related nuclear cataract .…”
Section: Applications Of Msi In the Understanding Of Pathogenesismentioning
confidence: 99%
“…The idea that proSAAS plays a role in neurodegenerative proteostasis is further supported by human transcriptomics studies, which indicate increased proSAAS expression during AD progression ( Mathys et al, 2019 ). Increased levels of proSAAS have also been found in brain tissues of patients with CAA ( Inoue et al, 2017 ), as well as in models of neurodegenerative diseases including horses ( McGorum et al, 2016 ) and rats ( Chatterji et al, 2014 ). Lastly, recent data from our laboratory indicate that cellular proSAAS levels are upregulated following ER and even heat stress ( Shakya et al, 2020 ); interestingly, in parallel experiments, similar upregulation was not observed for 7B2.…”
Section: B2 and Prosaasmentioning
confidence: 99%
“…MSI was also used in peptidomics, for example, determining the distribution of endogenous peptides in brain tissues (Chatterji et al, ; Chatterji & Pich, ). In the study of a rat model of Usher's disease, a rare disease considered to be a leading cause of deaf‐blindness in humans worldwide, cryosections of brain tissue were analyzed to differentiate between healthy and diseased rats (Chatterji et al, ). Three factors were found to be important for the success of peptide quantitation.…”
Section: Msi‐based Proteomicsmentioning
confidence: 99%